2018
DOI: 10.1002/ana.25361
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol decreases duration of spreading depolarization and spreading ischemia after aneurysmal subarachnoid hemorrhage

Abstract: Objective: Traditionally, angiographic vasospasm (aVS) has been thought to cause delayed cerebral ischemia (DCI) after aneurysmal subarachnoid hemorrhage (aSAH). However, successful treatment of aVS alone does not result in improved neurological outcome. Therefore, there may be other potential causes of poor neurological outcome, including spreading depolarization (SD). A recent study showed beneficial effects of cilostazol on DCI and neurological outcome. The present prospective clinical trial and experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…Thereafter, a relative oligemia to 135 (IQR: 76–182) % occurred (Figure 2A). The typical pattern of SI (Dreier et al, 1998; Dreier, 2011; Sugimoto et al, 2018) was not observed in any of the SDs under hypoxia that preceded the terminal one.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Thereafter, a relative oligemia to 135 (IQR: 76–182) % occurred (Figure 2A). The typical pattern of SI (Dreier et al, 1998; Dreier, 2011; Sugimoto et al, 2018) was not observed in any of the SDs under hypoxia that preceded the terminal one.…”
Section: Resultsmentioning
confidence: 78%
“…These typically occur following non-spreading depression of activity after onset of anoxia/severe ischemia, and thus historically are termed ‘anoxic SD’ (van Harreveld, 1946; Leão, 1947; Bures and Buresova, 1957; Marshall, 1959). However, SD can transform into intermediate and persistent types even in well-nourished tissue by the mechanism of SI, which reflects inverse neurovascular coupling (Dreier et al, 1998, 2001; Dreier, 2011; Sugimoto et al, 2018). Here, we observed SI in response to terminal SD in two out of four hypoxic animals in which the terminal SD preceded the CA.…”
Section: Discussionmentioning
confidence: 99%
“…Neurophysiologic changes have previously been proposed as one pathway contributing to DCI progression [27] and new or worsening EAs are representative of poor cerebral metabolism [9][10][11][12] and have been shown to predict DCI [4,5]. Furthermore, these EEG abnormalities have previously been linked to cortical spreading depolarizations [10][11][12], which themselves have been associated with DCI and subsequent poor outcome [13,28,29]. Prior literature illustrates that new or worsening EAs are strongly co-linear with subsequent DCI, which is likely an in-hospital complication intermediate in the chain of events leading to poor outcome, rather than a confounder [6].…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that volume expansion with IV fluids and nimodipine, a calcium channel blocker used clinically to prevent DCI, could antagonize spreading ischemia through effects on the microcirculation [55]. In collaboration with other investigators in a clinical-translational paper, they found that the phosphodiesterase-3 inhibitor cilostazol could decrease the duration of spreading ischemia in their rat model of SAH and SDs [57]. Finally, a different group targeted SDs using valproate and found that valproate mitigated injury from induced SD in an endovascular perforation model of SAH [56].…”
Section: Therapeutic Studies In Animalsmentioning
confidence: 91%